STUDENTS’ PERCEPTIONS OF ENGLISH TEACHERS’ TEACHING STRATEGIES IN SECONDARY SCHOOL EFL CLASSROOMS - Utary Rustam; Hasbiyah Srianah Amir; Dewi Yuliani Lukman; Syaiful Syaiful (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
Students’ perceptions provide valuable insights into how teaching strategies are experienced in English as a Foreign Language (EFL) classrooms. This study examined secondary school students’ perceptions of the teaching strategies employed by English teachers at SMPN 2 Parepare, Indonesia. A descriptive quantitative survey was conducted with 172 ninth-grade students selected through simple random sampling. Data were collected using a 30-item questionnaire adapted from Barnes and Orlich’s framework of effective teaching strategies (Cronbach’s α = 0.91). The findings revealed a mean perception score of 92.31 out of 120, indicating positive perceptions across all eight instructional dimensions. Teacher–Student Relationship received the highest mean score (M = 3.24), whereas Feedback and Assessment received the lowest (M = 2.93), although both remained within the positive category. These findings highlight students’ positive perceptions of English teachers’ instructional practices and suggest the importance of maintaining supportive teaching strategies while strengthening feedback and assessment practices.